Therapeutic prospects and potential mechanisms of Prdx6: as a novel target in musculoskeletal disorders - Sun, Hong; Xu, Chao; Xiong, Zhilin; Liu, Miao; Ning, Xu; Zhuang, Yong (Frontiers in Physiology, 2025)
With the global population aging, musculoskeletal disorders (MSDs) have posed significant physical and psychological health challenges for patients as well as a substantial economic burden on society. The advancements in conservative and surgical interventions for MSDs have been remarkable in recent years; however, the current treatment modalities still fall short of meeting the optimal requirements of patients. Recently, peroxiredoxin 6 (Prdx6) has gained considerable attention from researchers due to its remarkable antioxidative, anti-inflammatory, and anti-apoptotic properties. It has been found that Prdx6 is involved in multiple system diseases, including MSDs; however, the exact role of Prdx6 in MSDs is still lacking. This study aimed to summarize the structure, regulatory mechanism, and potential function of Prdx6. These findings may demonstrate Prdx6 as a novel target for inhibiting the advancement of MSDs.